Molecular tools to identify tropical mosses: a case study of the Brazilian species of Schlotheimia Brid. (Bryophyta, Orthotrichaceae). Issue 6 (18th August 2019) - Valente Valente, Daiane; Aguiar Saraiva Câmara, Paulo Eduardo; Peralta, Denilson Fernandes; Stech, Michael
Abstract : Species of the moss genus Schlotheimia are often difficult to identify morphologically, because it is necessary to study sporophytic characters and fertile plants are quite rare. In this paper, we aim to infer the potential of trn G-R, trn L-F, and ITS markers to resolve phylogenetic relationships and species delimitations within Schlotheimia in Brazil, using different tree-based analysis methods and Automatic Barcode Gap Discovery (ABGD). For the first time in bryophytes, the trn G-R spacer was sequenced together with the trn G intron ( trn G-R region). Furthermore, we aim to evaluate the morphological species concept based on the molecular data, to aid the on-going taxonomic revision of Schlotheimia in Brazil. The combined analysis of all three markers resolved 11 clades corresponding to Schlotheimia species, which was corroborated by ABGD and morphological characters. The best candidate marker for DNA barcoding was trn G-R due to its easy amplification and ability to discriminate all but one species. While trn G-R is sufficient for routine identification, the combination trn G-R + ITS should be used if all Brazilian Schlotheimia species are to be identified with high statistical support. The nuclear marker ITS was easy to amplify and more variable than the plastid markers, but a higher percentage of low quality sequences due to polynucleotide stretches or fungal contamination is a potential drawback. Trn L-F had a low discrimination potential. The analysis of the molecular markers investigated provides a baseline for the taxonomic revision of Schlotheimia and is an important tool for the identification of sterile specimens.